2019
DOI: 10.1002/bsl.2402
|View full text |Cite
|
Sign up to set email alerts
|

The impact of proficiency testing information and error aversions on the weight given to fingerprint evidence

Abstract: Fingerprint examiners regularly participate in tests designed to assess their proficiency. These tests provide information relevant to the weight of fingerprint evidence, but no prior research has directly examined how jurors react to proficiency testing information. Using a nationally representative sample of American adults, we examined the impact of proficiency testing information on the weight given to the opinions of fingerprint examiners by mock jurors considering a hypothetical criminal case. The finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 13 publications
6
26
0
Order By: Relevance
“…Other studies observed the same effect observed here: people's risk preferences, or views on error rates, affect how they view evidence in criminal cases (Mitchell & Garrett, 2019). Although the criminal justice system adopts a heightened "beyond a reasonable doubt" burden of proof and thus treats false convictions as more serious than false acquittals, individuals may not share that normative view.…”
Section: Iva Risk Preferencessupporting
confidence: 69%
“…Other studies observed the same effect observed here: people's risk preferences, or views on error rates, affect how they view evidence in criminal cases (Mitchell & Garrett, 2019). Although the criminal justice system adopts a heightened "beyond a reasonable doubt" burden of proof and thus treats false convictions as more serious than false acquittals, individuals may not share that normative view.…”
Section: Iva Risk Preferencessupporting
confidence: 69%
“…These concerns primarily relate to genuinely held opinions that are plausible, but ultimately incorrect or insufficiently reliable. For example, low-quality opinions are those that are given without sufficient evidence that the underpinning science is repeatable, reproducible, or accurate (PCAST 2016); that is expressed incorrectly or without appropriate qualification (NRC 2009), where the proficiency of the examiner has not been demonstrated (Garrett and Mitchell 2018;Martire and Edmond 2016) and where biasing contextual information has not been appropriately disclosed or managed (Dror 2016;NRC 2009). Conversely, high(er)quality opinions are those based on foundationally valid methods and techniques, that are expressed using valid terminology, and that appropriately disclose assumptions and limitations (NRC 2009).…”
Section: Evidence Quality Evaluation In Forensic Contextsmentioning
confidence: 99%
“…Compounding this problem, laypeople tend to believe that forensic science errors are exceptionally rare (38). Hence, jurors tend to trust forensic evidence (39,40), even if it was analyzed using an unvalidated technique (41) and even after being explicitly informed of its limitations (42).…”
mentioning
confidence: 99%